THE RELATIONSHIP BETWEEN FINANCIAL LITERACY AND THE CONSUMPTIVE BEHAVIOR OF SATYAGAMA UNIVERSITY STUDENTS - I Nyoman Suri Adnyana; Rahmatullah Rahmatullah; Didi Sukardi; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to analyze the relationship between financial literacy and the consumer behavior of Satyagama University students. The research method used a quantitative approach with data collection techniques through the distribution of questionnaires to active students of Satyagama University. Data were analyzed using descriptive and correlation analysis to determine the relationship between financial literacy levels and student consumer behavior. The results showed that financial literacy has a negative relationship with consumer behavior, where students with better financial literacy levels tend to have more rational and controlled consumption behavior.